HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KECEMASAN KELUARGA PASIEN DI RUANG BEDAH RS PERTAMINA BINTANG AMIN BANDAR LAMPUNG - Umi Romayati Keswara; Eka Trismiyana; Riska Wandini (Malahayati Nursing Journal, 2019)
ABSTRACT : THE COMMUNICATION RELATIONSHIP OF NURSE THERAPEUTIC WITH THE ANXIETY OF PATIENT’S FAMILY AT THE SURGERY ROOM OF PERTAMINA BINTANG AMIN HOSPITAL BANDAR LAMPUNG   Backround: Family care in the hospital will cause stress, anxiety and depression for the family. Therapeutic communication techniques that nurses can use to lower anxiety are listening and caring so effective in reducing anxiety and accelerating healing.Purpose: of this study is to know the therapeutic communication relationship of nurses with the anxiety of the patient's family in the surgery room of Pertamina Bintang Amin Hospital Bandar Lampung.Methods: The type of this research was quantitative. The research design was analytical survey with cross sectional survey. Sampling technic used was accidental sampling. The statistical test used chi-square test.Result: obtained most of respondents felt that nurse therapeutic communication was not good, as many 30 people (60%) and most of respondents experienced the anxiety as many 29 people (58%). Bivariate analysis result obtained that there was the communicatoin relationship of nurse therapeutic with the anxiety of patient’s family at the surgery room of Pertamina Bintang Amin Bandar Lampung Hospital Year of 2017 with p-value α (0,0030,05) with OR = 7,667.Conclusion: The suggestion given was to improve the nurse therapeutic communication to resolv the anxiety of patient’s family. Keywords      : Therapeutic communiation, Family’s anxiety, Nurse